The response of Na+/K+ -ATPase of human erythrocytes to green laser light treatment - Kassák, P; Sikurová, L; Kvasnicka, P; Bryszewska, M (Physiological research, 2006)
The objective of this study was to investigate the response of Na(+)/K(+)-ATPase of human erythrocytes to green laser irradiation. Effects of green laser light of fluences 9.5-63.3 J.cm(-2) and merocyanine 540-mediated laser light treatment were studied. Isolated erythrocyte membranes (protein concentration of 1 mg/ml) were irradiated by Nd:YAG laser (532 nm, 30 mW) and then incubated in a medium with 2 mM ATP for 30 min. Activity of ATPase was determined colorimetrically by measuring the colored reaction product of liberated inorganic phosphate and malachite green at 640 nm. Contribution of Na(+)/K(+)-ATPase to overall phosphate production was determined using ouabain. A positive effect of green laser light on Na(+)/K(+)-ATPase activity was observed. The dependence of enzymatically liberated inorganic phosphate on light fluence showed a linear correlation (R(2)=0.96, P=0.0005) for all fluences applied (9.5-63.3 J.cm(-2)). On the other hand, MC 540-mediated phototreatment caused a suppression of enzyme activity.
Keywords: erytrocyty; sodíko-draslíková ATPasa; Color; Sodium-Potassium-Exchanging ATPase; Pyrimidinones; fluorescenční barviva; Humans; Fluorescent Dyes; pyrimidinony; lidé; Low-Level Light Therapy; lasery; laserová terapie s nízkou intenzitou světla; Lasers; Erythrocytes; barva